2019
DOI: 10.1007/s00484-019-01811-0
|View full text |Cite
|
Sign up to set email alerts
|

What prevails in climatic response of Pinus sylvestris in-between its range limits in mountains: slope aspect or elevation?

Abstract: The roles of slope orientation and elevational temperature gradient were investigated for Scots pine (Pinus sylvestris L.) growth in the middle of its growth range, where these factors can significantly modulate microclimate and thus plant growth. We assumed that slope orientation causes more complex and severe effects than elevation, because it influences all three main factors of plant growth: light, heat and moisture. In addition to the total ring width, the earlywood and latewood width and latewood ratio w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
0
10
0
1
Order By: Relevance
“…This might be linked with the species-specific predisposition and with the climate type of the study area. In the continental climate, the cambial activity rate exhibits unimodal and asymmetrical kinetics with a maximum closer to the onset of the season coinciding with earlywood development (Popkova et al, 2018 ; Fonti et al, 2020 ), which lowers the latewood proportion for Scots pine to about one-third of the ring as observed in Scots pine trees growing in various natural zones of the region (Zhirnova et al, 2020 , 2021 ). Therefore, the TRW climatic response was more focused on earlywood than latewood, and seasonal interval of significant correlations (i.e., May to the first half of June) has been consistent with the production of earlywood tracheids.…”
Section: Discussionmentioning
confidence: 99%
“…This might be linked with the species-specific predisposition and with the climate type of the study area. In the continental climate, the cambial activity rate exhibits unimodal and asymmetrical kinetics with a maximum closer to the onset of the season coinciding with earlywood development (Popkova et al, 2018 ; Fonti et al, 2020 ), which lowers the latewood proportion for Scots pine to about one-third of the ring as observed in Scots pine trees growing in various natural zones of the region (Zhirnova et al, 2020 , 2021 ). Therefore, the TRW climatic response was more focused on earlywood than latewood, and seasonal interval of significant correlations (i.e., May to the first half of June) has been consistent with the production of earlywood tracheids.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we found significant climatic response in radial growth and wood anatomy of both species in the study area. Cell production and radial growth is limited mainly by soil water availability in May-June (positive correlations with precipitation and negative ones with temperature), latewood CWT has positive correlation with temperature in the end of summer [29,44,45].…”
Section: Methodsmentioning
confidence: 99%
“…The measuring points were located in places where the position of the upper forest line was not exposed to major and direct landform-related impacts, such snow avalanches, debris flows, landslides, etc. All measuring points had similar exposure to minimize the difference in solar radiaton (Buffo 1972;Zhimova et al 2019). In addition to the 8 measuring points mentioned above, air temperature measurements were carried out at the Hala Gąsienicowa research station, which is located at 1520 m a.s.l.…”
Section: Study Areamentioning
confidence: 99%
“…The forest line is not only of interest to foresters or, more generally, botanists, but also to researchers dealing with inanimate nature, for example geomorphologists and climatologists (Fabijanowski 1955;Myczkowski 1964;Pawłowski 1972;Balon 1991aBalon , 1991bBalon , 1995Barry 1992;Heikkinen et al 1995;Kotarba 1987;Krzemień et al 1995;Piękoś-Mirkowa and Mirek 1996;Barber et al 2000;Kirchhefer 2000;Becker and Bugmann 2001;Jodłowski 2007;Körner 2009;Lebourgeois et al 2010;Jochner et al 2018;Kelsey et al 2018;Zhimova et al 2019). The latter group of researchers, in particular, have closely fol-lowed changes in the position of the individual vegetation zones, including the forest line, as indicators of climate change.…”
Section: Introductionmentioning
confidence: 99%